Environmentally sustainable practices and products: analysis of content of information released in a circulated magazine in Brazil - Damasceno, Angélica Lucas; Prado Filho, José Francisco do; Camargos, Silvana Prata (Revista Gestão da Produção Operações e Sistemas, 2008)
This study presents a survey of printed advertisements with environmental appeal. The content of these advertisements was analyzed to identify environmental appeal and its vehicles of exposition. A weekly magazine of national circulation was used. The criteria developed by Eneias (2005) were used to delimit the ecological advertisements considering the visual and discursive appeals of the enviromental area, and the criteria used by Guimarães (2006), which were: the product/service relationship with the biophisical enviroment; promotion of a green life style without highlighting the product/service, and disclosure of the corporations enviromental responsibility image. The analysis was performed on from May (2005) to April (2007). As a result, this work presents a general view of the use of enviromental marketing strategies in Brazil, showing that the economic sectors that used this resource the most were the banking sector, mining-metallurgy and cosmetics. Companies are more concerned with the images they give costumers than the ecological attributes of their products. This study found that the less used appeal was the one that seeks to promote the enviromentally correct life style, normally used by Non Governmental Organizations. Key-Words: Environmental Marketing; Printed Advertisements; Environmental Appeal